Notes on the Flora of Bihar and Orissa - Saxena, H. O. (Indian Forester, 1976)
The paper describes two new records for Bihar and Orissa, namely Ageralum, houstonianum Mill. and Cyperu pulchellus R.Br;, and four new records for Orissa besides notes on Lindernia hisutta (Benth.) Wettst., Portulaca tuberosa Roxb., shuteria densiflora Benth. and Suaeda maritima dumort.